Understanding the connection between conformational changes of peptides and equilibrium thermal fluctuations. Issue 5 (18th January 2017) - Soler, Miguel A.; Zúñiga, José; Requena, Alberto; Bastida, Adolfo
Abstract : A novel computational method to analyze jointly the vibrational fluctuations and the conformational dynamics of peptides and proteins in water at equilibrium. Abstract : Despite the increasing evidence that conformational transitions in peptides and proteins are driven by specific vibrational energy pathways along the molecule, the current experimental techniques of analysis do as yet not allow to study these biophysical processes in terms of anisotropic energy flows. Computational methods offer a complementary approach to obtain a more detailed understanding of the vibrational and conformational dynamics of these systems. Accordingly, in this work we investigate jointly the vibrational energy distribution and the conformational dynamics of trialanine peptide in water solution at room temperature by applying the Instantaneous Normal Mode analysis to the results derived from equilibrium molecular dynamics simulations. It is shown that conformational changes in trialanine are triggered by the vibrational energy accumulated in the low-frequency modes of the molecule, and that excitation is caused exclusively by thermal fluctuations of the solute–solvent system, thus excluding the possibility of an intramolecular vibrational energy redistribution process.